Quantitative Risk Assessment of Foot-and-Mouth Disease (FMD) Virus Introduction Into the FMD-Free Zone Without Vaccination of Argentina Through Legal and Illegal Trade of Bone-in Beef and Unvaccinated Susceptible Species - Marcos, Andrea; Perez, Andrés M. (Frontiers in Veterinary Science, 2019)
Argentina is a foot-and-mouth disease (FMD)-free country divided into five zones associated to disparate epidemiological situations and control strategies. Two zones are free from FMD with vaccination and three without vaccination. Quantitative risk assessment was used here to estimate the risk of introduction of FMD virus (FMDV) into the Argentine FMD-free without vaccination zone via legal or illegal trade of bone-in beef and non-vaccinated live animals from the FMD-free zone with vaccination of the country. Because, trade of those commodities between those two zones is currently banned in Argentina, the analysis here will help evaluating the impact of relaxing such prohibition in the national regulation and the impact of illegal trade. Results suggest that if the volume of incoming bone-in beef is equal to the volume of deboned beef that enters the non-vaccinating zone, the annual risk of an FMDV introduction to the zone without vaccination will be low (0.0017). Indeed, the risk of introduction via illegal trade is 6.9 times higher compared to legal trade. Similarly, the annual risk was also low for movement of live sheep and goat (0.0059) and swine (0.007) when the FMDV was assumed to be adapted to bovine and when a serological test was performed prior to movement. The implementation of a serological test to ovine reduces 19 times the risk for FMDV introduction. In conclusion, the risk of introduction of FMDV into the FMD-free zone without vaccination through bone-in beef, sheep, goat and swine with certain requirements, such as serological testing, is nil. If legal trade was allowed, the incoming risk may even be lower, compared to the current scenario of prohibiting the introduction. Results are likely due to the controls associated to legal trade, and the subsequent reduction of illegal trade. Consequently, results suggest that a policy of incentive and facilitation of good practices may be more effective in preventing FMDV introduction into a free zone than prohibition of trade.